Zero-Dimensional Schemes in the Plane - Ballico, E. (Sarajevo Journal of Mathematics, 2024)
Let ZP^2 be a zero-dimensional scheme. Fix tN. In this paper we study the following question: find assumptions on Z and t such that h^1(I_A(t)) <h^1(I_Z(t)) for all AZ and check if t does not exist for a certain class of schemes Z. 2010 Mathematics Subject Classification. 14N05.